Identifying the Water Quality of the Great Northern River, the Middle Section, Using the Canadian Water Quality Index (Latakia University Journal -Biological Sciences Series, 2023)
This Study Aims at identifying the water quality of the middle section of the Great Northern River by calculating the values of the Canadian water quality index in three sites (S1, S2, S3) depending on a set of physical chemical and biological indicators, (cI, BOD, TDS, TH, T, PH, Total coliforms, NH4+, SO4-2). Samples were taken during six months at a rate of once a month. The values of the Canadian index were 39.8 in the site S1, 41.5 in the site S2 and 41.4 in the site S3. All these values were within the range 0-45 according to the table of the Canadian index values, hence, the water quality is very bad in the three sites. Results of the statistical analysis showed a good relationship between the values of the tow indexes, BOD and Total coliforms, and the values of both of them exceeded the limits according to the Syrian standards for drinking water and metrology for the year 2007. The main source of pollution in the studied area is the sewage which was confirmed by the field visits where it was found that there are seven sites of contamination with untreated sewage.